Persepsi Wisatawan Terhadap Daya Tarik Wisata Lapangan Puputan Badung I Gusti Ngurah Made Agung, Kota Denpasar, Bali - Febriani, Putu Diana; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2024)
The research is located in Lapangan Puputan Badung I Gusti Ngurah Made Agung. The research was conducted to find out what tourism product are in Lapangan Puputan Badung I Gusti Ngurah Made Agung, and also to know tourist perceptions of Lapangan Puputan Badung I Gusti Ngurah Made Agung. This research is very important and can be a reference for stakeholders for tourism development in Lapangan Puputan Badung I Gusti Ngurah Made Agung. This research uses a quantitative descriptive approach with primary and secondary data. The data were collected through observation, online questionnaires, documentation, and literature study. It uses purposive sampling with a close-ended questionnaire using the Likert Scale. Lapangan Puputan Badung I Gusti Ngurah Made Agung as a tourist attraction has fulfilled the components that must be owned by a tourist attraction, including attractions, accessibility, amenities, and ancillary. This research results indicated that most tourists pay attention to the attractions variable in Lapangan Puputan Badung I Gusti Ngurah Made Agung, because the percentage of highest and lowest perceptions by tourists are on the attractions variable in Lapangan Puputan Badung I Gusti Ngurah Made Agung. Therefore, it can be concluded that even though Lapangan Puputan Badung I Gusti Ngurah Made Agung has attraction, accessibility, amenities, and ancillary as a tourist attraction, it still needs to evaluate the management of Lapangan Puputan Badung I Gusti Ngurah Made Agung, so that can meet what is expected and needed by tourists. Keywords: Tourist Perception, Tourist Attraction, Lapangan Puputan Badung, City Park